Heat Transfer: Volume 4 2005
DOI: 10.1115/ht2005-72007
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Heat Exchanger Efficiency Monitoring

Abstract: The performance of heat exchangers degrades with time due to fouling or deposition of material on the heat transfer surface. The fouling of critical exchangers in manufacturing plants results in a significant cost impact in terms of production losses, energy efficiency, and maintenance costs. While most plants monitor their exchangers to some degree, the ability to effect real and sustainable improvements requires four components: (1) real time monitoring; (2) an advance warning mechanism; (3) the ability to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…• The cooling water circulation pumps should be equipped with an inlet strainer to avoid impeller damage and to prevent the heat exchangers from getting plugged due to objects carry over (Prasad et al, 2005).…”
Section: Case Study 6 -Define Design Premises Of Cooling Water Systemsmentioning
confidence: 99%
“…• The cooling water circulation pumps should be equipped with an inlet strainer to avoid impeller damage and to prevent the heat exchangers from getting plugged due to objects carry over (Prasad et al, 2005).…”
Section: Case Study 6 -Define Design Premises Of Cooling Water Systemsmentioning
confidence: 99%
“…With this information in mind, monitoring and detecting fouling in the aircraft ECS heat exchanger remains a challenge and will be tackled in chapters to follow. Several documents [95][96][97][98][99][100][101] are available on heat exchanger monitoring processes.…”
mentioning
confidence: 99%
“…Model-based fault detection and diagnosis can be classified into two main categories: quantitative model-based methods or qualitative model-based methods as defined in Figure 80 (111]. There is an abundance of literature on process fault detection and diagnosis (with regards to detection of fouling) ranging from analytical methods ( [97], [98], [100], [101], and [112 -123]) to statistical approaches ( [99], and [124][125][126]). The most common methods of detecting faults in the heat exchanger are based on assessment of the heat transfer coefficient, the pressure drop, the flow rates, the temperature drop and the weight of the plates.…”
mentioning
confidence: 99%
“…However, statistical inference methods can be used to estimate the model parameters based on data obtained from real time monitoring of the fouling process [14].…”
Section: Case Studymentioning
confidence: 99%
“…Zubair et al [12,13] have studied statistical models to describe heat transfer component degradation. Prasad et al reported an algorithm developed by GE capable of predicting degradation in heat exchangers [14].…”
Section: Introductionmentioning
confidence: 99%